How elite swimmers control their hand propulsive force and arm coordination with increasing velocity during front crawl - Matsuda, Y.; Sakurai, Y.; Ichiawa, H.; lkuta, Y.; Kudo, S. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to investigate the change in the intensity and timing of the hand propulsive force by using pressure sensor and motion capture systems as increasing velocity during front crawl swimming. Twelve elite swimmers participated in this study. The swimmers swam three different velocity; i.e. 70%, 80% and 900h of maximal velocity. The propulsive force of both hands were recorded by multiple pressure sensors, and whole body kinematics was measured by using motion capture system. The average propulsive force during the pull and push phase, and thus, total stroke cycle increased as increasing swimming velocity. The non-propulsive phase decreased as increasing swimming velocity. Swimmers increase their swimming velocity with both increasing their hand propulsive force and decreasing their arm non-propulsive duration during a stroke cycle of front crawl swimming.